Duration of reproductive years and time since menopause were associated with metabolic syndrome in postmenopausal parous women of Chinese ancestry. Issue 2 (February 2020) - Yu, Weihui; Hu, Xiang; Yang, Lijuan; Pan, Wei; Deng, Huihui; Chen, Xiong; Zhou, Qi; Chen, Shuoping; Si, Qiya; Chen, Xueqin; Li, Qianqian; Shen, Feixia; et al.
Abstract: Objective: Although duration of reproductive years and time since menopause were previously implicated in the metabolic syndrome, the evidence is more limited. Few of the previous studies were able to take into account related reproductive variables simultaneously. The aim of the present study was to explore the influence of these two reproductive factors on the prevalence of metabolic syndrome in postmenopausal parous women from Southeast China. Methods: In all, 1, 536 postmenopausal parous women were recruited. Self-reported information about reproductive status, including age at menarche, age at menopause, number of children, prepregnancy body weight, and oral contraceptive use, was collected, and duration of reproductive years and time since menopause were calculated. Clinical parameters related with metabolic syndrome were also measured. Results: Longer duration of reproductive years was significantly related with increased presence of the metabolic syndrome (odds ratio [OR] 1.570, 95% confidence interval [CI] 1.091, 2.259 for tertile 2 group; OR 1.850, 95% CI 1.163, 2.944 for tertile 3 group; P for trend = 0.010). Women with more than 20 years since menopause were more likely to experience metabolic syndrome (OR 2.422, 95% CI 1.109, 5.286, P  = 0.026) and elevated blood pressure (OR 3.239, 95% CI 1.406, 7.458, P  = 0.006) when compared with those with less than 10 years since menopause. Conclusions: Longer duration of reproductive years and time since menopause were associated with higher prevalence of metabolic syndrome in postmenopausal parous women from Southeast China.